(untitled) (Ágora de Heterodoxias, 2025)
The goals of the sustainable goals in the 2030 agenda are translated into actions to be developed in research, so the objective of the study is to analyze whether there are statistically significant differences in basic education children based on anger, sadness and worry as part of socio-emotional skills. Quantitative research with a cross-sectional design used a non-probabilistic sample of 381 students, 194 girls and 187 boys, with an age range of 9 to 13 years, ( = 10.38, σ = 1.124) enrolled in five basic education schools in the State of Mexico. To measure the variables of the study, three instruments were used (α= .80). An analysis of percentages, as well as contrast of means between boys and girls, was carried out through the student’s t statistic, identifying that there are no statistically significant differences according to sex. This study provides evidence of a positive change in the perception of gender roles. The reduction of stereotypes associated with the management of emotions, especially in children’s education, represents progress towards gender equality with respect to the goals established in the Sustainable Development Goals, especially in the third, fourth and fifth goals